Description and life-cycle of Taenia lynciscapreoli sp. n. (Cestoda, Cyclophyllidea) - Haukisalmi, Voitto; Konyaev, Sergey; Lavikainen, Antti; Isomursu, Marja; Nakao, Minoru (ZooKeys, 2016)
A new species of tapeworm, Taenia lynciscapreoli sp. n. (Cestoda, Cyclophyllidea), is described from the Eurasian lynx (Lynx lynx), the main definitive host, and the roe deer (Capreolus capreolus and C. pygargus), the main intermediate hosts, from Finland and Russia (Siberia and the Russian Far East). The new species was found once also in the wolf (Canis lupus) and the Eurasian elk/moose (Alces alces), representing accidental definitive and intermediate hosts, respectively. The conspecificity of adult specimens and metacestodes of T. lynciscapreoli sp. n. in various host species and regions, and their distinction from related species of Taenia, was confirmed by partial nucleotide sequences of the mitochondrial cytochrome c oxidase subunit 1 gene. Morphologically, T. lynciscapreoli sp. n. can be separated unambiguously from all other species of Taenia by the shape of its large rostellar hooks, particularly the characteristically short, wide and strongly curved blade. If the large rostellar hooks are missing, T. lynciscapreoli may be separated from related species by a combination of morphological features of mature proglottids. It is suggested that T. lynciscapreoli has been present in published materials concerning the tapeworms of L. lynx and L. pardinus in Europe, but has been misidentified as Taenia pisiformis (Bloch, 1780). Taenia lynciscapreoli sp. n. has not been found in lynx outside the range of roe deer, suggesting a transmission pathway based on a specific predator–prey relationship. The present study applies a novel, simple approach to compare qualitative interspecific differences in the shape of rostellar hooks.